(untitled) - Redwood, John (England, 1980)
This work attempts to provide a theoretical background to these policies and to illustrate ways in which they can be pursues further across the whole gamut of public enterprise.
Keywords: Sở hữu chính phủ,Government ownership; Lịch sử,History; Thế kỷ 21,20th century; Nước Anh,Great Britain